2012
DOI: 10.1111/1758-2229.12009
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of increased temperature and acidification on bacterioplankton community composition during a mesocosm spring bloom in the Baltic Sea

Abstract: Despite the paramount importance of bacteria for biogeochemical cycling of carbon and nutrients, little is known about the potential effects of climate change on these key organisms. The consequences of the projected climate change on bacterioplankton community dynamics were investigated in a Baltic Sea spring phytoplankton bloom mesocosm experiment by increasing temperature with 3°C and decreasing pH by approximately 0.4 units via CO₂ addition in a factorial design. Temperature was the major driver of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
84
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 60 publications
14
84
3
3
Order By: Relevance
“…Effect of warming on community structure We found that a thermal shift from 40 to 46 1C caused a dramatic change in community composition (as reflected within the community proteome; Figure 2, Supplementary Figure S2), as has been reported in other warming studies in soils, oceans and freshwater (for example, Deslippe et al, 2012;Yergeau et al, 2012;Lindh et al, 2013;Luo et al, 2013;von Scheibner et al, 2014). Nearly a quarter of the organisms had a greater than twofold change in abundance between temperatures.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Effect of warming on community structure We found that a thermal shift from 40 to 46 1C caused a dramatic change in community composition (as reflected within the community proteome; Figure 2, Supplementary Figure S2), as has been reported in other warming studies in soils, oceans and freshwater (for example, Deslippe et al, 2012;Yergeau et al, 2012;Lindh et al, 2013;Luo et al, 2013;von Scheibner et al, 2014). Nearly a quarter of the organisms had a greater than twofold change in abundance between temperatures.…”
Section: Discussionsupporting
confidence: 80%
“…Many microbial community studies have evaluated the effect of warming on overall community structure and on specific metabolic processes such as respiration (for example, Zogg et al, 1997;Finke and Jørgensen, 2008;Rose et al, 2009;Yergeau et al, 2012;Lindh et al, 2013;Wu et al, 2013;von Scheibner et al, 2014). Far fewer studies have comprehensively assessed functional responses across the entire community (for example, using 'omic' approaches (Luo et al, 2013;Toseland et al, 2013) or functional gene arrays (Yergeau et al, 2012;Tu et al, 2014)).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the abundance of planktonic Bacteroidetes also increases in response to increased temperature and/or CO 2 content (and thus decreased pH) in both mesocosms and natural seawater environments (850)(851)(852). These results further emphasize the niche segregation and ecophysiological distinction of these two key groups of marine bacteria and indicate their distinct roles in marine carbon cycling and other critical biogeochemical processes, especially under the scenario of global change.…”
Section: Marine Roseobacter Clade Bacteria and Bacteroidetes In Surfamentioning
confidence: 58%
“…Prediction is not a simple task as such a kind of shift may result in the lagoon functioning. In fact, variation in the response of phytoplankton communities exposed to warming may be a consequence of differences in species composition or physiological status of the algae (Lindh et al, 2013). Furthermore, what is stressed in recent literature is the need for a more complete picture and consideration of the responses of the entire food web and interactions therein to describe and predict the complex and sometimes counterintuitive responses of plankton to global climate changes (Vidussi et al, 2011;Boyce et al, 2015).…”
Section: Discussionmentioning
confidence: 99%